A Systematic Review on Inclusive Education of Students with Visual Impairment - Hisae Miyauchi (Education Sciences, 2020)
This was a systematic review on the inclusive education of students with visual impairment. This study focused on two of the most addressed topics: the perceptions of general education teachers and challenges faced by students with visual impairment in accessing academic subjects. It synthesized the findings of 18 peer-reviewed articles published in English from 1980 to 2020. General education teachers’ attitudes toward the inclusion of students with visual impairment were both positive and negative and were influenced by teacher-, student-, and environment-related factors. Feeling unprepared, one of the main teacher-related factors, seemed to have a great effect. In terms of access to academic subjects, the most discussed subjects were Mathematics, Science, and Physical Education. Although students with visual impairment seemed to be studying at or above their grade level, their exclusion from participation in classroom activities was apparent. Unfortunately, these challenges lead to short- and long-term consequences. Key elements in increasing accessibility to subjects were: general education teachers possessing a generic set of effective pedagogical strategies, effective teaching-learning tools, and external support. The importance of teacher training and a holistic support system were emphasized.